Doing Business in Juba 2011 - World Bank; International Finance Corporation (Washington, DC, 2013)
Doing Business in Juba 2011 is part of the International Finance Corporation (IFC) Sudan Investment Climate Program. The program aims to reduce administrative and regulatory barriers to business, attract new investments in sectors such as agribusiness and hydro power, provide small and medium enterprises with management training, and develop access to credit and leasing. Doing Business in Juba 2011 functions as a kind of cholesterol test for the regulatory environment for domestic businesses. A cholesterol test does not tell us everything about the state of our health. But it does measure something important for our health. And it puts us on watch to change behaviors in ways that will improve not only our cholesterol rating but also our overall health. Doing Business uses a simple averaging approach for weighting sub-indicators and calculating rankings. Other approaches were explored, including using principal components and unobserved components. The principal components and unobserved components approaches turn out to yield results nearly identical to those of simple averaging. The tests show that each set of indicators provide sufficiently broad coverage across topics. Therefore, the simple averaging approach is used.